(untitled) (LEARNing Landscapes, 2012)
This paper explores the rich learning that happens between defined learning spaces, such as that between formal curriculum and informal projects. Here we apply the notion of "hybrid space," to understand how such in-between learning spaces can facilitate a shift in participatory roles for college students engaged in a community media project. This study also highlights the ways in which media as a production medium can further transform the learning experience.